Enhancing speaking skills through the use of authentic materials: an empirical study - Guambo Yerovi, Enrique Jesús; Mantilla Cabrera, Luis Francisco (Dominio de las Ciencias, 2026)
This study examines the impact of authentic materials on improving oral skills in A2-level learners of English as a foreign language (EFL). A mixed-methods design, incorporating both quantitative and qualitative approaches, was used to assess the effectiveness of real-world materials, such as podcasts, news articles, and videos, in developing oral proficiency. During a six-week intervention, 30 participants in a Mechanical Engineering program were exposed to these materials. Pre-test and post-test results showed a significant improvement in oral skills, with an average increase of 20 points. The study also found a high level of student satisfaction, with 85% reporting increased motivation to learn and 90% indicating they would recommend these materials to others. These findings highlight the value of incorporating authentic materials into EFL teaching to foster oral fluency, cultural competence, and student engagement.